Pengaruh Permainan Papan Cocok Terhadap Kemampuan Mengenal Warna pada Anak Usia 4-5 Tahun di TK Negeri Pembina Ki Hajar Dewantoro Kecamatan Dungingi - Marmin Adam; Yakob Napu; Yenti Juniarti (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This study aimed to determine whether there is an Effect of Matching Board Games on the Color Recognition Skills in Children Aged 4-5 Years at TK Negeri Pembina Ki Hajar Dewantoro, Dungingi Subdistrict. This study used a quantitative experimental method. The research findings involving 15 children revealed that there was an increase in the results of the Pre-test and Post-Test. In this case, it was observable from the Pre-test data obtaining an average value of 16.06 and a standard deviation of 2.604 and the Post-Test data was with an average value of 21 and a standard deviation of 3.461. in reference to these findings, the respondents who were samples in this study obtained an increase in average results from the pre-test to the post-test.